2017
DOI: 10.1177/2156869317725891
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Social Control of People with Serious Mental Illness: An Empirical Verification and Extension of Theory

Abstract: Mental health services and psychiatric professional values have shifted in the past several decades toward a model of client autonomy and informed consent, at least in principle. However, it is unclear how much has changed in practice, particularly in cases where client behavior poses ethical challenges for clinicians. Drawing on the case of clients’ sexual behavior and contraception use, we examine whether sociological theories of “soft” coercion remain relevant (e.g., therapeutic social control; Horwitz 1982… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 51 publications
1
18
0
Order By: Relevance
“…In particular, our findings show that many spouses intensely engage in the acquisition of mental health care via attunement to the emergence of mental health symptoms, expression of concern about those symptoms, and attempts to convince a spouse that the problems are serious enough to require professional care. This finding is in line with Horwitz’s (1982) theory of “therapeutic social control,” in which family members and professionals are expected to work to get those with mental health issues to undergo treatment (see also Perry, Frieh, and Wright 2018). Future research should explore whether these same processes occur in other family and social network ties such as parent-child relationships, siblings, and friendships.…”
Section: Discussionsupporting
confidence: 82%
“…In particular, our findings show that many spouses intensely engage in the acquisition of mental health care via attunement to the emergence of mental health symptoms, expression of concern about those symptoms, and attempts to convince a spouse that the problems are serious enough to require professional care. This finding is in line with Horwitz’s (1982) theory of “therapeutic social control,” in which family members and professionals are expected to work to get those with mental health issues to undergo treatment (see also Perry, Frieh, and Wright 2018). Future research should explore whether these same processes occur in other family and social network ties such as parent-child relationships, siblings, and friendships.…”
Section: Discussionsupporting
confidence: 82%
“…We did not seek directly the perspectives and experiences of sexuality, intimacy and relationships for individuals experiencing psychological distress and illness. The perspectives of individuals engaged in mental health services have been explored both in Australia (Quinn and Happell, 2015) and elsewhere (Blalock and Wood, 2015;Deegan, 1999;Perry et al, 2017), and the experiences identified in those studies are reflected in our findings with clinicians. That we did not systematically collect information about participants' sexual orientation or identity may be considered a limitation.…”
Section: Limitationsmentioning
confidence: 75%
“…through the threat of force, mandatory medical procedures, forced medication use, or involuntary commitment) (Perry et al . 2017). We might consider coercive practices a thing of the past – yet in 2019, one in seven mental health service users in Australia are under an involuntary treatment order, one in five service users are involuntarily treated in residential care, and one in two overnight hospitalisations are involuntary (Australian Institute of Health and Welfare 2019).…”
Section: Mental Illness Assemblagesmentioning
confidence: 99%
“…This leads to the second mechanism of control, conciliation (persuasion by the major to adhere to a recommendation, often through relationship) (Perry et al . 2017). ‘Person‐centred treatment plans’ or ‘collaborative goal setting’ used by recovery‐oriented community mental health services may unintentionally persuade people with mental illness to envision and work towards a normative vision of recovery (Perry et al .…”
Section: Mental Illness Assemblagesmentioning
confidence: 99%
See 1 more Smart Citation